IMPROVING TEACHER PERFORMANCE THROUGH A GOOD LEADERSHIP AND MOTIVATIONAL APPROACH - Rahmannisa Juita Usmar; Achadi Budi Santosa Santosa (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2022)
Teacher performance is important in an educational institution. Optimal teacher performance has been shown to affect school quality and improve student achievement. This study aims to determine the effect of the principal's leadership style and work motivation on the performance of elementary school teachers. The population sample includes teachers at private schools in the Sungai Penuh Regency. The data is taken by questionnaire. The results showed a positive and significant influence between leadership style and teacher performance, with the value of sig. 0.041 < 0.05. Work motivation has a positive and significant effect on teacher performance, with a value of sig. 0.000 < 0.05. There is a positive and significant influence between leadership style and work motivation simultaneously on teacher performance, with a value of sig. 0.000 is less than 0.05. The results of this study indicate that principals need to continue to encourage teachers through a kind and sympathetic approach so that their performance can be more optimalTeacher performance is important in an educational institution. Optimal teacher performance has been shown to affect school quality and improve student achievement. This study aims to determine the effect of the principal's leadership style and work motivation on the performance of elementary school teachers. The population sample includes teachers at private schools in the Sungai Penuh Regency. The data is taken by questionnaire. The results showed a positive and significant influence between leadership style and teacher performance, with the value of sig. 0.041 < 0.05. Work motivation has a positive and significant effect on teacher performance, with a value of sig. 0.000 < 0.05. There is a positive and significant influence between leadership style and work motivation simultaneously on teacher performance, with a value of sig. 0.000 is less than 0.05. The results of this study indicate that principals need to continue to encourage teachers through a kind and sympathetic approach so that their performance can be more optimal.